2010
DOI: 10.1007/s13213-010-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Technological and probiotic characteristics of Lactobacillus plantarum strains isolated from traditionally produced fermented vegetables

Abstract: The technological and probiotic characteristics of a number of Lactobacillus plantarum strains (previously isolated and identified from traditionally produced fermented vegetables) were compared, with the aim of identifying potential starter cultures to be used for the fermentation of vegetables. The L. plantarum strains were differentiated by their plasmid profiles; 12 separate strains with different plasmid profiles were examined. Other than survival in different concentrations of NaCl, the technological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 35 publications
6
27
0
2
Order By: Relevance
“…Traditional fermented vegetables are produced by natural microflora, e.g. LAB, through physicochemical changes that include conversion of sugars in the plant into primarily lactic acid under anaerobic conditions (Karasu, Simsek, & Con, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fermented vegetables are produced by natural microflora, e.g. LAB, through physicochemical changes that include conversion of sugars in the plant into primarily lactic acid under anaerobic conditions (Karasu, Simsek, & Con, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the LAB quickly proliferate, produce acid, become the dominant species under the anaerobic conditions and inhibit the growth of Enterobacteriaceae and Bacillus. At the end of the fermentation, abundant LAB become the dominate microorganism and the fermentation of pickles remains stable (Karasu et al, 2010;Panagou and Katsaboxakis, 2006). Therefore, it is worth identifying the LAB isolated from pickles for development of industrial starter for pickle fermentation.…”
mentioning
confidence: 99%
“…Similarly, Papamanoli et al (2003) reported that L. plantarum strains which were isolated from naturally fermented dry sausages could grow at 6.5-10% NaCl. On the other hand, Karasu et al (2010) showed that L. plantarum strains isolated from traditionally produced fermented vegetables tolerated up to 8% NaCl. The highest salt concentration tested (12%) exerted a strong effect on LAB strains, as most of the tested strains were completely or significantly inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only a few studies have attempted to study the selection of appropriate starter cultures for pickle fermentation (e.g., Çon and Karasu, 2009;Karasu et al, 2010). In our recent study (Bağder Elmacı et al, 2015), we isolated and identified 152 LAB strains from fermented pickles produced in Çubuk region of Ankara, Turkey.…”
Section: Introductionmentioning
confidence: 99%